Barriers and facilitators to recruitment in mental health services: Care coordinators' expectations and experience of referring to a psychosis research trial. (25th September 2014) - Bucci, Sandra; Butcher, Isabelle; Hartley, Samantha; Neil, Sandra T.; Mulligan, John; Haddock, Gillian
<x xml:space="preserve">Abstract</x> Objective High‐quality research trials are necessary to provide evidence for the effective management of mental health difficulties, but successful recruitment can be challenging. Design This qualitative study examines the perceived barriers and facilitators to referring mental health service users to research trials. Seven care coordinators (n = 7) who facilitated the recruitment of participants to a cognitive behaviour therapy – informed psychosis intervention trial were interviewed. Method Demographic information was collected by questionnaire and a semi‐structured guide was used to explore barriers and facilitators to referring to a partially randomized participant preference trial. Qualitative data were thematically analysed. Results Four key themes, each with a number of sub‐themes, were identified: (1) engage the care coordinator in the recruitment process, (2) barriers to referring to research studies, (3) facilitators to referring to research studies; (4) organisational constraints impact on implementing research outcomes into routine clinical practice. Conclusions Understanding the barriers and facilitators to recruitment in mental health research could improve recruitment strategies. Our findings highlight the need for researchers' to closely consider their recruitment strategies as service users are not always given the choice to participate in research. Several key recommendations are made based on these findings in order to maximize successful recruitment to research studies. Overall, we recommend that researchers' adopt a flexible, tailor‐made approach for each clinical team to ensure a collaborative relationship is developed between research staff and clinicians. Practitioner points A qualitative approach to understanding recruitment challenges provides a useful opportunity to explore the barriers and facilitators to recruiting participants to research studies. These findings have practical implications that highlight the need for a collaborative partnership between researchers and clinical services. Understanding the challenges and issues related to recruitment can help researchers consider strategies to overcome recruitment issues. More research with a larger sample, across a broader population and in different mental health services is required.